RAYLEIGH SCATTERING BY AQUEOUS COLLOIDAL SILICA AS A CAUSE FOR THE BLUE COLOR OF HYDROTHERMAL WATER - Ohsawa S.; Kawamura T.; Takamatsu N.; Yusa Y. (My University, 2002)
Thermal waters in hydrothermal ponds, bathing pools and the brines of geothermal electric power plants commonly have a characteristic blue color. Although many researchers have assumed that the blue color is due to a colloidal suspension and/or absorption by dissolved ferrous iron or by water itself, there has been no specific effort to identify the physical nature of this phenomenon. We have tested, in synthetic and natural solutions, whether aqueous colloidal silica is responsible for the blue color. Aqueous colloidal silica is formed by silica polymerization in thermal waters of the neutral-chloride type which contain initially monomeric silica in concentrations up to three times above the solubilities of amorphous silica. The hue of the blue thermal waters in the pools tested agrees with that of a synthesized colloidal silica solution. Grain-size analyses of aqueous colloidal silica in the blue-colored thermal waters demonstrate that the color is caused by Rayleigh scattering from aqueous colloidal silica particles with diameters (0.1-0.45 μm) smaller than the wavelengths of visible radiation.
Keywords: THERMAL WATER; BLUE COLOR; COLLOIDAL SILICA; RAYLEIGH SCATTERING